Temporal variation of freshwater as control of mangrove in Banyuasin Estuary, South Sumatra, Indonesia - HERON SURBAKTI; I WAYAN NURJAYA; DIETRIECH G BENGEN; TRI PRARTONO (Society for Indonesian Biodiversity, 2023)
Abstract. Surbakti H, Nurjaya IW, Bengen DG, Prartono T. 2023. Temporal variation of freshwater as control of mangrove in Banyuasin Estuary, South Sumatra, Indonesia. Biodiversitas 24: 1502-1510. The Banyuasin Estuary receives much freshwater, which transports low-salinity water from upstream to the sea through the rivers that flow along the area. The interaction between the freshwater mass from the river and the highly saline seawater mass moving toward the estuary will affect the condition of the mangroves in the region. This study aims to estimate the freshwater runoff from the two main rivers (Musi River and Banyuasin River) into the Banyuasin Estuary in different seasons, at high and low tides, and their impact on the mangroves present in both estuaries. The interaction between the freshwater and seawater masses can be explained using the freshwater fraction and transect methods used for mangrove zonation analysis. This research focuses on the mouth of the Musi River and the Banyuasin River. The present study showed the influence of freshwater fraction at the mouth of the Musi River is very strong in all seasons, dominated by oligohaline and mesohaline conditions. In contrast, the mouth of the Banyuasin River is dominated by mesohaline and polyhaline conditions. Altogether, ten species of mangroves have been found in the Banyuasin Estuary. Of which, low saline tolerant species, namely Nypa fruticans and Sonneratia caseolaris, are predominant, whereas salt tolerant species, namely Avicennia marina, are predominant in the mouth of the Banyuasin River.